2018
DOI: 10.1053/j.gastro.2018.03.063
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement in Gastrointestinal Symptoms After Cognitive Behavior Therapy for Refractory Irritable Bowel Syndrome

Abstract: In a randomized controlled trial, we found that a primarily home-based version of CBT produced significant and sustained gastrointestinal symptom improvement for patients with IBS compared with education. Clinicaltrials.gov no.: NCT00738920.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 36 publications
2
131
0
7
Order By: Relevance
“…Cognitive behavioral therapy is a known therapy to treat neurological disorders such as mood disorders, anxiety, and depression . As IBS patients often report similar neurological disorders, the efficacy of CBT to improve the quality of life of IBS patients may not be surprising . Moreover, anecdotal clinical evidence suggests that CBT is an efficient intervention to treat visceral pain in IBS patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Cognitive behavioral therapy is a known therapy to treat neurological disorders such as mood disorders, anxiety, and depression . As IBS patients often report similar neurological disorders, the efficacy of CBT to improve the quality of life of IBS patients may not be surprising . Moreover, anecdotal clinical evidence suggests that CBT is an efficient intervention to treat visceral pain in IBS patients.…”
Section: Discussionsupporting
confidence: 55%
“…Clinical evidence suggests that CBT also improves in the overall symptomatology of patients with irritable bowel syndrome (IBS) . Irritable bowel syndrome a common gastrointestinal disorders characterized by chronic abdominal pain, due to increased visceral sensitivity, and abnormal bowel habits.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relative lack in therapist availability, clinical implementation of these therapies is still limited. Recent attempts to reduce resource use without compromising effectiveness may assist in making psychological treatment more widely available; for example, group hypnotherapy, Internet‐delivered exposure‐based CBT, and home‐based CBT . In that light, it will be interesting to explore whether these developments can affect long‐term quality of life and well‐being in patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to GI symptom severity, we found that quality of life did not improve over time in those that were Rome III-negative at Internet-delivered exposure-based CBT, 50 and home-based CBT. 51 In that light, it will be interesting to explore whether these developments can affect long-term quality of life and well-being in patients with IBS.…”
Section: Clevers Et Al Recently Evaluated Longitudinal Symptom Changementioning
confidence: 99%
“…Cognitive behavioural therapy is considered to be safe, but AEs have not been well documented in clinical trials . However, a 2018 clinical study of cognitive behavioural therapy in patients with IBS (n = 436) reported one AE of suicide attempt, which was not considered to be related to treatment . The number needed to harm for cognitive behavioural therapy has not been published.…”
Section: Resultsmentioning
confidence: 99%